2022
DOI: 10.1155/2022/1338082
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Ethiopian Bread Wheat (Triticum aestivum L.) Genotypes in Southern Ethiopia

Abstract: Ethiopia is not self-sufficient to meet its increasing wheat demand from domestic production partly due to a lack of improved seeds. Efforts are undertaken to fill the gap through off-season production of wheat using supplemental irrigation and modern cultivars adapted to arid areas. This study was carried out to evaluate the genetic variability and adaptability of 15 Ethiopian bread wheat genotypes at different agroecologies in Wolaita and Dawuro zones, Ethiopia. The field experiment was conducted at three lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Understanding this interaction can help breeders to develop more adaptable and high-yielding varieties. Similarly, previous studies showed differences among genotypes in terms of the number of days to maturity, number of days to heading, plant height, spike length, number of seeds per spike, thousand seed weight, and grain yield per plots [ 22 , 23 ]. Other studies on bread wheat [ 14 , 83 ] also showed highly significant differences among genotypes, which aligns with the findings of our study.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Understanding this interaction can help breeders to develop more adaptable and high-yielding varieties. Similarly, previous studies showed differences among genotypes in terms of the number of days to maturity, number of days to heading, plant height, spike length, number of seeds per spike, thousand seed weight, and grain yield per plots [ 22 , 23 ]. Other studies on bread wheat [ 14 , 83 ] also showed highly significant differences among genotypes, which aligns with the findings of our study.…”
Section: Discussionsupporting
confidence: 54%
“…However, closing the gap between supply and demand to improve bread wheat production level and self-sufficiency is a primary national goal [ 21 ]. Plant breeders are always trying to improve grain yield, quality, and adaptability to both abiotic and biotic stresses [ [22] , [23] , [24] ].…”
Section: Introductionmentioning
confidence: 99%
“…This study has revealed varying levels of CV g in durum wheat germplasm, with some traits exhibiting high-to-moderate CV g values, offering opportunities for improvement through selective breeding. Conversely, the CV g estimates were low for other traits, implying limited genetic variability that may hinder traditional selective breeding methods [37]. Additionally, the difference between CV p and CV g values has highlighted the influence of environmental factors on trait variability, particularly for traits like CC, MT, FLA, and yield components, excluding TKW.…”
Section: Discussionmentioning
confidence: 99%